American feminist playwrights a critical history - Burke, Sally (Twayne's critical history of American drama, 1996)
The history of America's feminist playwrights is as old as the history of the nation. Since the incorporation of the United States in the late 1700s, scores of women have dramatized the plight of women in a culture dominated by the interests of its men. Mercy Otis Warren, a patriot of the Revolution, was not only the country's first woman playwright but also its first feminist playwright. Warren and the dramatists Susanna Rowson and Anna Cora Mowatt, who followed her in the 19th century, addressed in their plays such feminist concerns as the objectification of women, the silencing of their voices, and their psychological and physical abuse - concerns that continue to appear in the plays of contemporary feminist playwrights